Digital Humanities Pedagogy : Practices, Principles and Politics - Brett D. Hirsch
Academic institutions are starting to recognize the growing public interest in digital humanities research, and there is an increasing demand from students for formal training in its methods. Despite the pressure on practitioners to develop innovative courses, scholarship in this area has tended to focus on research methods, theories and results rather than critical pedagogy and the actual practice of teaching. The essays in this collection offer a timely intervention in digital humanities scholarship, bringing together established and emerging scholars from a variety of humanities disciplines across the world. The first section offers views on the practical realities of teaching digital humanities at undergraduate and graduate levels, presenting case studies and snapshots of the authors' experiences alongside models for future courses and reflections on pedagogical successes and failures. The next section proposes strategies for teaching foundational digital humanities methods across a variety of scholarly disciplines, and the book concludes with wider debates about the place of digital humanities in the academy, from the field's cultural assumptions and social obligations to its political visions. Digital Humanities pedagogy broadens the ways in which both scholars and practitioners can think about this emerging discipline, ensuring its ongoing development, vitality and long-term sustainability.